ChemInform Abstract: Chemical and Photochemical Functionality of the First Molecular Bismuth Vanadium Oxide. Issue 1 (3rd January 2013) - Tucher, Johannes; Nye, Leanne C.; Ivanovic‐Burmazovic, Ivana; Notarnicola, Antonio; Streb, Carsten
Abstract The first molecular bismuth vanadium oxide cluster compound H3 [{Bi(dmso)3}4V13O40] ·≈4DMSO is synthesized by addition of an aqueous Bu4NOH solution to a hot solution of Bi(NO3)3 and (Bu4N)3[H3V10O28] in DMSO/2% H2O (80 °C, 1 h, 91% yield).